Factors Affecting Fertilizer Purchase Decision: Problem of Agricultural Marketing - Roy, Debdulal Dutta; Choudhary, Kaushik (PYC Nepal Journal of Management, 2016)
Fertilizer market is an important component of agricultural economy of the Asian countries. This study was carried out to explore factors affecting decision to purchase fertilizer by the farmers. Data were collected from 200 farmers through five-point Likert-type questionnaire constructed for current study. The questionnaire was used to seek farmers’ opinion on the significance of the selected determinants to purchase fertilizer. These determinants are – price, fertilizer quality, brand, advertisement, soil quality, crop quality and landscapes. Results revealed that farmers gave more importance on quality of crops, fertilizer and landscape than price and advertising.